Case Report: Micronized purified flavonoid fraction [Daflon]-induced bradycardia - Rodrigues, Jhennyfer Aline Lima; Graças, Jonathas Pereira das; Machado, Gledson de Oliveira (Frontiers in Pharmacology, 2025)
IntroductionFlavonoids are oral venoactive drugs frequently prescribed to relieve the symptoms of chronic venous disorders. Micronized purified flavonoid fraction (MPFF, commercial Daflon 1000 mg) is a preparation that contains mainly diosmin and a small fraction of hesperidin. Both active ingredients are flavonoids, known for their anti-inflammatory and antioxidant properties.ObjectiveWhether the MPFF can alter hemodynamic behavior was examined.MethodsDaflon 1,000 mg was administered for 60 days, and the hemodynamic parameters were measured during the circadian cycle.ResultsThere were no significant differences for systolic blood pressure (100.1 ± 10.6 mmHg vs. 104.8 ± 7.7 mmHg) or diastolic blood pressure (73.8 ± 3.1 mmHg vs. 76.4 ± 6.6 mmHg) before and after MPFF intake, respectively (p > 0.05). However, in sharp contrast, the heart rate reduced significantly after intake of MPFF (88.8 ± 10.5 bpm vs. 79.3 ± 9.7 bpm; p < 0.05). The mean blood pressure was negatively correlated with the heart rate (HR) in the afternoon (r = −0.450, p = 0.016). During this period, there was a decrease in vein inflammation and varicosity, as shown by magnetic resonance imaging.ConclusionWe reported a new effect of MPFF as an attenuator of the heart rate. Because venous insufficiency decreased during the observed drug administration period, further studies are needed to examine whether the ability of diosmin and hesperidin to reduce vein disorders is directly linked to their action on heart rate.